Evaluasi Dalam Pendidikan Sebagai Alat Ukur Hasil Belajar - Alif Achadah (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
Education is one of the organizations that aims to make someone better in a variety of things so they can compete in the times. Education is said to be successful if the education produces output or graduates who are able to answer the challenges of the times. The aim of national education is to educate the nation's life and efforts to develop the whole person. The effort to improve the intelligence of national life is in various fields of life such as economics, politics, security, health, and so forth. While the success of education can be known by the evaluation process which is currently better known as the educational evaluation. Related to the evaluation process, the evaluation process in its development does not only concern student achievement but in this case the evaluation of learning also involves all kinds of things that exist in educational institutions including the extent to which the goals in the educational institution have been achieved.